A CASE STUDY OF BEAR REINTRODUCTION IN PAKISTAN: ART AND POLITICS IN CONSERVATION - Fakhar-i-Abbas; Afsar Mian; Naim Ashraf Raja; Safdar Shah; Jan-Schmidt-Burbach (Journal of Animal and Plant Sciences, 2020)
Bears are Pakistan’s largest terrestrial animals. Conservation status of brown bears is least concerned and black bear is vulnerable in the world, and critically endangered (brown) (Ahmed et.al. 2013: Sheikh and Molur 2004) and threatened in Pakistan. It is reported that roughly 92% of past black bear habitat is now empty or without them. Similarly 30% previously known distribution has now lost its population in Pakistan. Considering the problems this species is facing, a reintroduction plan was organized in which the confiscated bear cubs from poachers were raised in a specialized and least human contact enclosure. Considering regional habitat difficulties, the sites were properly studied and discussed. Due to an appropriate monitoring system, five rehabilitated bears were readied for release in those habitats in the last three years. Monitoring of the released individuals confirmed their survival and success in their adaptation. The first year release was not discussed publicly so complaints or any negative impact was never discussed. Second year release because of the involvement of the country’s prime minister went public. The media itself reported positively. The conservationists unanimously opposed the release for their own reasons. The second released bears were several times reported as poached, road killed, hunted with their parts sold in the market and five times destruction caused by them was reported at an area of our 50,000 square kilometers. This report is being presented with a hope that politics in conservation efforts could be reduced. Silent conservation efforts are more successful for nature but do not aware masses for future motivation and real impact, it is done with loud and clear message the fellow conservationists turn into competitions and they try to fail the efforts.
Keywords: Asian black bear. Ursus thibetanus. Reintroduction. Rehabilitation. Human wildlife conflict. Bear conservation. Bears population management. Population management. Bears of Pakistan